Pengembangan Instrumen Sikap Peduli Lingkungan Siswa pada Materi Makhluk Hidup - Hasibuan, Nurkhadizah; Hariyani, Mimi (Journal of Practice Learning and Educational Development, 2026)
Research instruments have a great influence on a research because that is where the truth of the research results lies. If the research instrument is wrong, it can be ascertained that the instrument cannot measure what should be measured. The instrument is useful for taking data from the research carried out. This study reviews valid and consistent and reliable instruments in providing research data related to students' environmental care attitudes which was developed consists of five indicators, namely: 1) Hard work to protect nature, 2) Initiative to protect the environment, 3) Respect for health and hygiene, 4) Wise in using natural resources and 5) Responsibility for the environment. The research methodology used in this study is Research and Development (R&D) research. To evaluate feasibility, a media feasibility tool was used to measure the efficacy of environmental care instruments, with melibatkan sampel 25 siswa. Penilaian ini dilakukan berdasarkan data ilmiah yang dikumpulkan melalui interaksi langsung dengan peserta. Analisis data dilakukan dengan menggunakan SPSS Versi 24.00 untuk validitas dan reliabilitas instrumen Windows. Hasil penelitian ini menyatakan bahwa seluruh item kuesioner valid dan reliabel dengan nilai reliabilitas tinggi seluruh studi konstruk Cronbach Alpha (0,955 > 0,6). So, these figures provide information that this study has produced a quality instrument that can be used to evaluate students' attitudes to care for the environment in the teaching and learning process at Sd 032 Kualu.